Adherence to dietary and lifestyle measures and glycemic control in Moroccan women with gestational diabetes: A cross-sectional study - Azargui , Hanane; El Arabi , Fatine; Al Ibrahmi, Btihaj; Boutahar, Kaltoum; Ikken, Youssef; Khal-Layoun, Soad; Bour , Abdellatif (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Gestational diabetes (GD) represents a frequent complication of pregnancy, affecting approximately 7-10% of pregnant women in Morocco. This study examined the relationships among therapeutic adherence, glycemic control, and weight changes in pregnant Moroccan women with GD.Methods: A cross-sectional study was conducted among 120 pregnant women diagnosed with GD. Sociodemographic, clinical, anthropometric data, and glycemic measurements were collected. Adherence to dietary and lifestyle measures (DLM) was assessed by standardized questionnaire, and participants were categorized based on adherence levels.Results: Initially, all participants (100%) had uncontrolled glycemia. After intervention, 53.3% of participants achieved glycemic balance. Adherence varied considerably: high for vegetable consumption (78.3%) and limiting sugars (75.8%), moderate to high for choosing low glycemic index foods (68.3%), moderate for controlling starchy foods (57.5%), and low for raw vegetables (40.8%). Significant correlations were identified between pre-gestational BMI and weight gain (r=-0.218; p=0.017), between weight gain and evening blood glucose (r=0.249; p=0.006), and between weight gain and overall adherence score (r=-0.236; p=0.009). Notably, 15% of participants experienced weight loss during pregnancy, raising concerns about inadequate nutritional intake.Conclusions: This study demonstrates that DLM alone can achieve glycemic balance in 53.3% of Moroccan women with GD. However, the 15% prevalence of gestational weight loss highlights the need for comprehensive monitoring that includes both glycemic and weight surveillance. These findings support culturally-adapted interventions, integrated weight monitoring protocols, and personalized nutritional counseling in GD management. Healthcare providers should maintain heightened vigilance for weight loss as a warning signal of inadequate nutritional status, even in women achieving apparent glycemic control.